Early versus delayed percutaneous coronary intervention in patients with non-ST elevation acute coronary syndromes. Issue 5 (August 2016) - Yudi, Matias B.; Ajani, Andrew E.; Andrianopoulos, Nick; Duffy, Stephen J.; Farouque, Omar; Ramchand, Jay; Gurvitch, Ronen; Lefkovits, Jeffrey; Freeman, Melanie; Brennan, Angela; Clark, David J.; Reid, Christopher; et al.
Abstract : Background: The optimal timing of angiography and percutaneous coronary intervention (PCI) in patients with non-ST elevation acute coronary syndromes (NSTEACS) remains uncertain. We sought to assess clinical characteristics and outcomes of patients in real-world contemporary practice who have early versus delayed PCI for NSTEACS. Methods: We analyzed baseline clinical and procedural characteristics of 4307 patients with NSTEACS who underwent PCI from the Melbourne Interventional Group registry. Patients were assigned to the early PCI group if intervention was performed within a calendar day of presentation. The delayed PCI group received an intervention after one calendar day, but within the index admission. We assessed 30 days and 12-month mortality, myocardial infarction, target vessel revascularization, and major adverse cardiovascular events. The safety endpoint was in-hospital bleeding. Results: Of the 4307 patients, 2210 (51%) received early PCI. The delayed PCI group were older (67±12 vs. 64±12, P <0.01), more likely to have biomarker elevation (70 vs. 66%, P <0.01), and had more comorbidities. There was no difference in efficacy at 30 days between the groups. At 12 months, delayed PCI was associated with higher mortality (4.6 vs. 3.3%, P =0.02), myocardial infarction (7.9 vs. 5.2%, P <0.01), and MACE (15.5 vs. 12.4%, P <0.01). On multivariate analysis, delayed PCI was not associated with increased mortality at 12 months (odds ratio 0.95, 95% confidence interval 0.7–1.3). Conclusion: In patients with stable NSTEACS treated with PCI, delayed intervention was performed in those who were older and had higher risk features. However, there appears to be no mortality hazard for these high-risk patients where PCI is delayed beyond the first 24 h after presentation and performed within the index admission.